Effects of oral maintenance chemotherapy and predictive value of circulating EBV DNA in metastatic nasopharyngeal carcinoma. (23rd February 2020) - Zhou, Han; Lu, Tianzhu; Guo, Qiaojuan; Chen, Yan; Chen, Mengwei; Chen, Yansong; Lin, Yingying; Chen, Chuanben; Ma, Liqin; Xu, Yun; Lin, Shaojun; Pan, Jianji
Abstract: Background/Objectives: Oral maintenance chemotherapy can effectively prolong overall survival (OS) in many types of metastatic cancer, but its role in metastatic nasopharyngeal carcinoma (mNPC) is unclear. In this study, the efficacy of oral maintenance chemotherapy in mNPC and the effectiveness of circulating tumor EBV‐DNA for screening patients were evaluated. Methods: Between June 2016 and December 2017, 141 patients with mNPC who received platinum‐based systemic chemotherapy were included (median follow‐up time, 21 months). Patients were classified into two groups according to the administration of oral maintenance chemotherapy. Plasma samples were collected before, during, and after treatment for the measurement of circulating EBV DNA. Results: The 2‐year OS was higher for patients who received maintenance chemotherapy than for patients without maintenance chemotherapy (78.9% vs 62.7%, P = .016). Patients with undetectable posttreatment EBV‐DNA after 4‐6 cycles of systemic chemotherapy (n = 73) had a higher 2‐year OS than that of patients with detectable EBV‐DNA (n = 68) (82.16% vs 51.45%, P = .001). For patients with undetectable posttreatment EBV‐DNA, OS was better for those with maintenance chemotherapy than for those without (86.7% vs 73%, P = .027). For patients with detectable posttreatment EBV‐DNA, maintenance chemotherapy did not improve outcomes (49.5% vs 55.4%, P = .824). The most common acute events were hematological toxicity, and all were tolerable and curable. Conclusions: Oral maintenance chemotherapy with S1 or capecitabine can improve OS in mNPC. Posttreatment EBV‐DNA was not only an independent prognosis factor for mNPC but also can screen out beneficiaries of maintenance chemotherapy. Abstract : Oral maintenance chemotherapy is beneficial in many types of metastatic cancer. In this retrospective analysis, we provide evidence that it improves overall survival in metastatic nasopharyngeal carcinoma (mNPC). Furthermore, we identified circulating EBV DNA as an independent prognostic factor and found that patients with undetectable EBV‐DNA but not with detectable EBV‐DNA may benefit from maintenance chemotherapy.